ANALYSIS OF MPASI MENU 4 BINTANG AS AN INNOVATION TO FULFILL NUTRITION FOR STUNTING CHILDREN 6 – 24 MONTHS IN THE WORKING AREA OF THE JOHAN PAHLAWAN PUSKESMAS WEST ACEH DISTRICT IN 2023 - Dian Febriani; Suci Eka Putri; Sufyan Anwar; Itza Mulyani (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2023)
Nutritional problems can occur in the life cycle starting from the womb until old age. Currently, Indonesia is facing multiple nutritional problems that must receive serious attention in handling. Malnutrition problems can cause health problems throughout the life cycle. One of the nutritional problems that occurs, especially in West Aceh Regency, is stunting. thus causing many children to have their growth and development hampered. The 4 star food menu is one way to provide nutrition for stunting toddlers. The aim of this research was to determine the knowledge, education, employment of mothers and eating patterns by providing MPASI with a 4 star menu as an innovation to fulfill nutrition for stunted children in the Johan Pahlawan Health Center working area, West Aceh Regency. The method used inThis research uses a qualitative method with a descriptive research type with an exploratory approach, namely conducting in-depth interviews.In general, not many people in the Johan Pahlawan Community Health Center work area are aware of the existence of the 4 star MPASI menu innovation for handling stunting. The relatively low level of education causes the mother's lack of knowledge in fulfilling nutrition according to the MPASI 4 Bintang Baduta menu. In handling stunting clowns, although there are those who know how to make the menu, they do not provide a 4 star MPASI menu due to low economic factors.